Therapeutic Communication and Post-Disaster Psychological Recovery Among Muslim Survivors - Zainun; Zeira Salim Ritonga; Nurrahman; Gusti Prabowo; Dori Chandra (Kartika: Jurnal Studi Keislaman, 2026)
Post-disaster psychosocial support in Muslim communities is still poorly understood, especially regarding the role of religious-based therapeutic communication in psychological recovery. The study examined the relationship between therapeutic communication and post-disaster psychological recovery while exploring culturally specific recovery mechanisms among Muslim disaster survivors. The design of the sequential explanation mixture method is used. Quantitative data were collected from 60 adult flash flood survivors using validated measures of therapeutic communication and psychological recovery, followed by in-depth interviews with 12 informants who were randomly selected to explain the quantitative findings. Quantitative analysis showed a positive yet modest relationship between therapeutic communication and psychological recovery, with stronger associations observed in future orientation and social functioning than in emotional stability. The qualitative findings identified five interrelated themes that highlight the importance of empathic listening, Islamic spiritual communication, peer social support, avoiding non-empathic responses, and tawakal-based expectations in the recovery process. The integration of the two strands suggests that therapeutic communication provides a relational foundation for recovery, while Islamic spiritual communication and community social support serve as a culturally based mechanism that reinforces psychological adaptation. The study proposes a bio-psycho-social-spiritual therapeutic communication model with practical implications for culturally responsive post-disaster psychosocial interventions in Muslim communities.